A low-cost, high-precision drip emitter suitable for low-pressure micro-irrigation systems - Chirgwin, Gavin Andrew; Sutton, Bruce (Irrigation science, 2019)
Potential low-cost micro-irrigation emitters appropriate for smallholder farmers in developing countries were the subject of a field experiment. Low-cost micro-irrigation technologies have been introduced with some success; however, further improvements are needed to increase adoption. The experiment evaluated three types of metal screw drip emitters (brass, zinc, and stainless steel), a conventional drip emitter, and a low-cost drip emitter (microtube). The effect of lateral flushing on emitter discharge and emitter uniformity was also evaluated. Emitter discharge, coefficient of variation ( C v ), emission uniformity (EU), emitter blockage rates, and crop yield ( Lactuca sativa ‘Toronto’) were the evaluation parameters. Screw emitter C v ranged from 5 to 27%, and the conventional emitter and microtube emitter C v were 9% and 29%, respectively. Blockage rates were significantly greater in the microtube, brass, and zinc emitters. Individual lettuce plant weight ranged from 0.676 to 0.912 kg/head for the three screw-based emitters, and 0.711 kg/head and 0.816 kg/head, respectively, for the microtube and conventional emitters. The stainless steel and conventional emitter performance were superior in all indices used to evaluate the emitters. Weekly flushing of laterals was found to be beneficial in optimizing emitter discharge and uniformity. Field evaluation demonstrated the potential use of metal-based screws as drip emitters.